Pengelolaan Persediaan dengan Menggunakan Metode EOQ dan MAPE pada CV. Miss Nomi Kreasi Indonesia - Liefofid, Yosefina Mouria Viany; Malinda Uscha, Cindy; Naibaho, Hastuti (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
Inventory has a strategic role as an essential asset for the company, especially in managing stock and controlling operational costs. Proper inventory management is key in balancing stock availability and the company's operational needs. CV. Miss Nomi Kreasi Indonesia faces challenges in aligning production planning with sales levels and market demand, which often results in excess or shortage of stock. This condition has a direct impact on increasing raw material and storage costs. This research focuses on applying forecasting methods to predict stock and production needs more accurately, using an approach of Exponential Smoothing to project inventory needs and Mean Absolute Percentage Error (MAPE) to measure the level of prediction accuracy. In addition, the method of Economic Order Quantity (EOQ) is used to determine the most efficient ordering quantity of raw materials. The research results show that the method of Exponential Single Smoothing with an alpha value of 0.2 has an accuracy rate of 41.03%, while the implementation of EOQ succeeded in reducing total annual costs from IDR 3,315,537,185.50 to IDR 1,866,260,675.68. This research proves that using appropriate forecasting and inventory management methods increases the company's operational efficiency and can provide practical solutions to overcoming the problems of suboptimal costs and stock. Using this approach, this research can provide an effective solution to increase company operational efficiency and reduce costs related to inventory management.